Using meta-abilities and tacit knowledge for developing learning based systems: A case study approach - Selamat, Mohamad Hisyam; Choudrie, Jyoti (Emerald Group Publishing Limited, 2007)
Purpose – Research has found that the implementation of learning-based systems development is a complex issue since it requires the input of employees at all levels of an organization. Successful implementation is a challenge for organizations as the basic training and education offered by them and the particular experiences of the individuals on their own and other factors such as fear and ignorance prevent such actions. For this purpose, the addition of other elements is also required. This research aims to identify and explain the usage of the elements that can encourage employees to contribute the inputs necessary for learning-based systems development. Design/methodology/approach – To achieve this aim, this research developed a conceptual framework based on the concepts of meta-abilities and tacit knowledge externalization and sharing.To illustrate the application of the framework in a real life setting, a case study approach that involved a large manufacturing organization in Malaysia was employed.Findings – The processes undertaken in the novel conceptual framework of this research should ensure that organizational information systems are subject to continual re-examination and modification. By internalizing a system’s operations, individuals can improve actions by acquiring better knowledge and understanding, which is the learning process. It was concluded that the future focus for the management of information in organizational learning should be towards the development of an individual’s meta-abilities and creating a suitable organizational culture and infrastructure such that knowledge sharing is promoted. Originality/value – Generally, this paper offers a contribution by illustrating the application of a conceptual framework in a practical situation; thereby demonstrating a theoretical and practical understanding of the integration of staff members into the IS development process.